Energetic analysis of simplified 2-position and 3-position North-South horizontal single-axis sun tracking concepts. (15th November 2017) - Gutiérrez, Sebastián; Rodrigo, Pedro M.
Highlights: Analysis of 2-position/3-position North-South horizontal single-axis sun trackers. 22 locations worldwide with latitudes up to 50° were evaluated. 2-position achieves irradiation gains from 6% to 27% relative to fixed system. 3-position achieves irradiation gains from 10% to 31% relative to fixed system. These trackers are an alternative to existing continuous trackers. Abstract: Sun trackers allow the energy yield of photovoltaic systems to be increased. Among the different types of sun tracking strategies, North-South horizontal single-axis sun trackers are of big interest nowadays, especially for their implementation in utility-scale photovoltaic plants. It is important to find concepts which simplify as much as possible these sun trackers. In this paper, an energetic analysis of two very simple tracking strategies, based on a 2-position or 3-position rotatory movement for the North-South horizontal single-axis tracker, is carried out for latitudes up to 50°. The tracker positions (morning/afternoon for 2-positions, or morning/noon/afternoon for 3-positions) change at pre-defined daily schedules and the tilt angle at the morning and afternoon periods is fixed. However, both the daily schedules and the tilt angles can be adjusted in the installation process, to maximize the annual irradiation capture in a given location. Such simple tracking concepts can be implemented without the need of illumination sensors, complex sun position calculations or continuous control of the motion. The energetic analysis was carried out over a set of 22 locations worldwide and the captured irradiation was compared to that of equator-pointed optimally tilted fixed systems and to that of the best energetically efficient North-South horizontal single-axis tracker, i.e. the continuous sun tracker. Results indicate that, depending on the analysed location, the 2-position tracker can provide between 41% and 74%, and the 3-position tracker can provide between 68% and 87% of the annual irradiation gains that the North-South horizontal single-axis continuous sun tracker achieves with respect to an optimally tilted fixed system. Therefore, these types of simplified tracking concepts, especially the 3-position tracker, can be seen as alternatives to existing North-South horizontal single-axis continuous sun trackers, providing significant energy gains with respect to fixed photovoltaic systems.